Developtment of Expansion Strategy, Case Study :Priere Footwear - Perdana Kesuma, Renaldi; Larso, Dwi (The Indonesian Journal of Business Administration, 2016)
Abstract. Priere Footwear is a leather shoes company built in 2013, it offers wide ranges of men’s leather shoes with classic design and high quality materials & constructions with extraordinary presentations. Their vision is to be the most reliable shoe brand and producers in South East Asia and their mission is to give best price/quality ratio products. In 2015 Priere Footwear face the latest problem of its business and it literally stop the business activities of Priere Footwear caused by suppliers problem which is the shoe manufacturers. The suppliers don’t follow the production schedule and quality standard causing trouble in production flow which impacts financially to the company. On the other hand Priere Footwear’s sales performance when the stock level is stable is excellent but it cannot maximized the opportunity. The methodologies for data gathering in this research is through observation, informal interviews with competitors, questionnaire that surveys random sample of 111 respondents.Writer also use literature research to add supporting datas related with Priere Footwear’s business such as middle class in Indonesia and the use of e-commerce in Indonesia. Data analysis is done with strategic management tools such SWOT analysis that shows result one of Priere Footwear’s strength is that they have good visual presentation and communication, and its weaknesses which are narrow revenue stream and overdependent on suppliers, while it also shows e-commerce trend as an opportunity and hyper competition as threats., Porter’s Five Forces Analysis that identifies suppliers as the strongest pressure in the industry, the other tools used are Business Model Analysis, Benchmarking of the competitors business model & TOWS Matrix that identifies the potential strategies relating the result of SWOT analysis and the last tools are STP & Marketing Mix Analysis to complete the analysis It was found out that the main problem of Priere Footwear that stop them to grow is its own business model causing the instability of the business and unable them to catch the opportunity in the industry. Results from analysis propose three expansion strategies to overcome the business issue of Priere Footwear which are Digital Marketing Strategy, E-Commerce Strategy and Vertical Integration Strategy which creates a modification in current Priere Footwear’s business model. The strategy implemented periodically from the third months of 2016 and finished in the tenth month of 2017 with the total budget needed of IDR 231 million. Keywords:Leather Shoes Business, Expansion Strategy, Business Model, SME